Ezekiel to Jesus Son of Man to suffering servant - Kavanagh, Preston; Parpola, Simo 1943- (Wipf & Stock, 2017)
This short book resolves the mystery of why Jesus chose to call himself Son of Man. Far earlier, the first Son of Man--the prophet Ezekiel--had met death as a Babylonian substitute king. Professor Simo Parpola's expert exposition about Assyrian substitutes prepares readers for the sacrifice first of Ezekiel and then, far later in time, of Jesus. Ezekiel was the Suffering Servant of Isaiah chapter 53, and had perished as a substitute to redeem the lives of his rebellious countrymen. Understanding Ezekiel's fate, Jesus chose the Son of Man title to exemplify his own redemptive mission. The authors of Mark, Luke, and Matthew subsequently framed their passion accounts so as to describe the suffering, death, and resurrection of Jesus as a latter-day substitute king. Most of this will come as news to students of both testaments of Scripture
Keywords: Jesus Christus; Bibel; Menschensohn; Son of Man; Jesus Christ / Name; Ezekiel / (Biblical prophet)